A longitudinal investigation of relational turbulence during the transition to college. Issue 3 (27th May 2022) - Shin, Matt; Goodboy, Alan K.; Dillow, Megan R.
ABSTRACT: As emerging adults transition to college, they must adapt to new circumstances, both academic and personal. For partners involved in a romantic relationship prior to attending college, this transition has important relational implications, including potential fluctuations in relational uncertainty and interdependence. Guided by relational turbulence theory (RTT), we conducted the present study to model growth trajectories of first-semester students' relationship parameters and experiences of relational turbulence during their transition to college (i.e., during the first eight weeks). Results of latent growth curve modeling revealed that students experienced higher levels of relational uncertainty, interference from a partner, and facilitation from a partner at the very beginning of their first semester in college, but each of these relationship parameters decreased over the first two months of the semester. Additionally, relational turbulence remained stable and did not change throughout the semester but correlated with contemporaneous relationship parameters as RTT predicts.